CHANGES IN THE STATUS OF UZBEKISTAN WOMEN IN SOCIETY IN THE CONDITIONS OF INDUSTRIALIZATION (1920-1930S) (Universal International Scientific Journal, 2026)
This thesis analyzes the changing position of women in society in the context of the industrialization policy implemented in Uzbekistan in the 1920s and 1930s. The study highlights the involvement of women in production sectors, their labor activity, and changes in their socio-political consciousness. It also provides a balanced analysis of the positive and negative aspects of this process, and draws historical conclusions.
Keywords: industrialization, women, social status, gender policy, labor activity, social activism, Uzbek SSR.